الصدمات النفسية وأنماط التعلق لدى المرضي المصابين بالصدفية - طاجين، سمية; صحراوي، عقيلة (جامعة عمار ثليجي بالأغواط, 2019)
انبثق موضوع بحثنا من الملاحظة الميدانية للمرضى الذين يعانون من مختلف الأمراض الجلدية، خاصة مرض الصدفية الذي يعتبر مرض جلدي ذو سوابق نفسية حيث يسميه الأطباء بالاكتئاب الجلدي. وذلك من خلال ملاحظة معاناتهم المرتبطة بمشكل قبوله كمرض جلدي مزمن يؤثر بشكل كبير على نوعية حياة المريض من جهة، وكيفية التسيير والتحكم في مختلف آثار الصدمات النفسية السابقة التي يعيشها من جهة أخرى. لتسليط الضوء على أهم هذه النقاط سيتم في هذا المقال عرض مفصل لحالة تعاني من الصدفية، وذلك بهدف التعرف على أهم الأحداث الصدمية التي عايشتها والأثار الناجمة عنها، مع تحديد نوعية التعلق ومدى تأثيرهما في ظهور وتفاقم أعراض مرض الصدفية لديها.
The choice of the theme of our Study results from the observation in the field of patients with various dermatoses, especially psoriasis is a cutaneous disease with a psychological antecedents, which is called by doctors a skin depression, by observing their suffering associated on one side with the problem of acceptance the chronicity of this disease, that affects considerably on the patient’s quality of life, and on other side to know how to mange and control the various effects of traumas that he experienced. In order to highlight the most important of these points In this article, will be a detailed presentation of case with psoriasis, in order to identify the most important traumatic events that have experienced , and determining the quality of attachment, and the extent of their impact on the emergence and aggravation of symptoms psoriasis.
Keywords: الاضطرابات النفسية -- الأمراض الجلدية -- الطب النفسي